(untitled) (Contemporary Journal of Social Science Review, 2025)
This study analyzes the principles and applications of Islamic jurisprudence (Fiqh) in the light of the Seerah of Prophet Muhammad. It highlights how the Prophet’s teachings, actions, and decisions provided the practical foundation for Islamic legal principles. The research discusses the major sources of Islamic law, including the Qur’an and Sunnah, and explains their role in shaping social, moral, economic, and legal systems. Using an analytical approach, the study also examines the contemporary relevance of Seerah-based jurisprudence in solving modern issues. It concludes that the Seerah of the Prophet remains an essential source for understanding and applying Islamic Fiqh in a balanced and practical manner.